Strengthening Student Character Education Through Investing Multicultural Values in Madrasah - Dian Rifia Jaya; Sofyan Sauri; Hendi Suhendraya Muchtar; Waska Warta (UIN Sunan Gunung Djati Bandung, 2019)
Strengthening character education through planting multicultural values into the basic values of culture and national character. The culture and character education of this nation can be developed from the religious values and ideology of the Indonesian nation which are formulated in the goals of national education. Character is the main key to developing quality resources. That way the character must be formed as early as possible.